Heritability of Body Weight in Crossbreed Chickens Between Bangkok Chickens and Laying Hens Based on Measurements at 8 Weeks of Age - Rusli Badaruddin; Rahim Aka; Hairil Azulyatno Hadini; La Ode Hermawan (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
This study aims to estimate the heritability of body weight in Bangkok crossbred chickens with laying breeds based on genetic variation components at 1–8 weeks of age. The data were analyzed using CRD (Completed Randomized Design) variance with a nested design (hierarchical structure) to obtain the variance components. The variance components were used to determine the estimated heritability of body weight in chickens resulting from crossbreeding between Bangkok and laying breeds. The results showed that environmental variance dominated in the early weeks, while dominant variance increased sharply in weeks 5 to 7. At week 8, additive genetic variance increased significantly (σ²s = 815,60), resulting in a high total heritability (ĥ²s+d = 0,61). These findings indicate that 8 weeks of age is the optimal point for selecting body weight in crossbred Bangkok chickens with laying breeds.